Design and implementation of bi-directional converter with internet of things control based reading - Wisam Dawood Abdullah; Raad Z. Homod; Abdulbasit H. Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this paper, a new technique to monitor and control bidirectional DC-DC converter was designed and implemented precisely. A prototype of a complete system is verified with efficient communication capabilities. This system is realized by integrating the internet of things (IoT) operating system and the bidirectional DC-DC converter. The IoT communication facilities further develop and extend the platform for this system. The DC-DC converter with the soft switching technique will then convert the battery voltage to a high voltage of 380V inverter bus in emergencies via boost converter mode. High-frequency toroidal transformer has been used for power level shifting and isolation between the primary and secondary sides of the transformer. The closed-loop control scheme is implemented in software by using a high-performance 32-bit STM32 micro controller. IoT technique is used to find current, voltage and perform the communication smoothly through Wi-Fi sensors to complete the design of the system. The results of the proposed system prove the effectiveness of the proposed system with high-performance specifications.